A Balance-Sheet Analysis of the Dutch Economy - Chen, Ruo. (Washington, D.C. : International Monetary Fund, 2021)
The Dutch economy is characterized by substantial financial balance sheets in the private sector. Uncommonly large gross financial assets and liabilities are found in the financial sector, whereas households own significant net financial wealth. The large gross financial assets and liabilities reflect a dominant role of multinational corporations (MNCs). Despite their size, these financial positions have not brought significant financial stability risks to the country. On the other hand, Dutch households' long balance sheets have been associated with depressed consumption and volatile real estate investment, which has probably exacerbated the cyclicality of the economy. The expected reform of the pension system is likely to change the way household balance sheets interact with private consumption.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Balance Sheet, Financial Accounts and Pension; Corporate Finance and Governance; Financial Institutions and Services; Investment Decisions; Net Financial Assets; Portfolio Choice